What do farmers' weed control decisions imply about glyphosate resistance? Evidence from surveys of US corn fields. Issue 5 (26th July 2017) - Wechsler, Seth J; McFadden, Jonathan R; Smith, David J
Abstract: BACKGROUND: The first case of glyphosate‐resistant weeds in the United States was documented in 1998, 2 years after the commercialization of genetically engineered herbicide‐resistant (HR) corn and soybeans. Currently, over 15 glyphosate‐resistant weed species affect US crop production areas. These weeds have the potential to reduce yields, increase costs, and lower farm profitability. The objective of our study is to develop a behavioral model of farmers' weed management decisions and use it to analyze weed resistance to glyphosate in US corn farms. RESULTS: On average, we find that weed control increased US corn yields by 3700 kg ha −1 (worth approximately US 255 ha −1 ) in 2005 and 3500 kg ha −1 (worth approximately US 575 ha −1 ) in 2010. If glyphosate resistant weeds were absent, glyphosate killed approximately 99% of weeds, on average, when applied at the label rate in HR production systems. Average control was dramatically lower in states where glyphosate resistance was widespread. CONCLUSION: We find that glyphosate resistance had a significant impact on weed control costs and corn yields of US farmers in 2005 and 2010. Published 2017. This article is a U.S. Government work and is in the public domain in the USA. Abstract : The presence of 1‐3 glyphosate‐resistant (GR) weed species has a small impact on the control provided by post‐emergent glyphosate. Larger numbers of GR weed species can decrease control substantially.